Incontinence medication response relates to the female urinary microbiota. Issue 5 (May 2016) - Thomas-White, Krystal; Hilt, Evann; Fok, Cynthia; Pearce, Meghan; Mueller, Elizabeth; Kliethermes, Stephanie; Jacobs, Kristin; Zilliox, Michael; Brincat, Cynthia; Price, Travis; Kuffel, Gina; Schreckenberger, Paul; et al.
Abstract Introduction and hypothesis Many adult women have resident urinary bacteria (urinary microbiome/microbiota). In adult women affected by urinary urgency incontinence (UUI), the etiologic and/or therapeutic role of the urinary microbiome/microbiota remains unknown. We hypothesized that microbiome/microbiota characteristics would relate to clinically relevant treatment response to UUI medication per os. Methods Adult women initiating medication treatment orally for UUI and a comparator group of unaffected women were recruited in a tertiary care health-care system. All participants provided baseline clinical data and urine samples. Women with UUI were given 5 mg solifenacin, with potential dose escalation to 10 mg for inadequate UUI symptom control at 4 weeks. Additional data and urine samples were collected from women with UUI at 4 and 12 weeks. The samples were assessed using 16S ribosomal RNA (rRNA) gene sequencing and enhanced quantitative urine culturing. The primary outcome was treatment response as measured by the validated Patient Global Symptom Control (PGSC) questionnaire. Clinically relevant UUI symptom control was defined as a 4 or 5 score on the PGSC. Results Diversity and composition of the urinary microbiome/microbiota of women with and without UUI differed at baseline. Women with UUI had more bacteria and a more diverse microbiome/microbiota. The clinical response to solifenacin in UUI participants was related to baseline microbiome/microbiota, with responders more likely to have fewer bacteria and a less diverse community at baseline. Nonresponders had a more diverse community that often included bacteria not typically found in responders. Conclusions Knowledge of an individual's urinary microbiome/microbiota may help refine UUI treatment. Complementary tools, DNA sequencing, and expanded urine culture provide information about bacteria that appear to be related to UUI incontinence status and treatment response in this population of adult women.